2018
DOI: 10.12688/wellcomeopenres.14914.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the context of diacidic motif DE as a signal for unconventional protein secretion in eukaryotic proteins

Abstract: Unconventional protein secretion (UPS) is an important phenomenon with fundamental implications to cargo export. How eukaryotic proteins transported by UPS are recognized without a conventional signal peptide has been an open question. It was recently observed that a diacidic amino acid motif (ASP-GLU or DE) is necessary for the secretion of superoxide dismutase 1 (SOD1) from yeast under nutrient starvation. Taking cue from this discovery, we explore the hypothesis of whether the diacidic motif DE, which can o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Of these two statistically significant observations, the triacidic motif, by coincidence, happens to be an extension of the observation of the diacidic motif (Cruz-Garcia et al, 2017) and our earlier attempt to find the context in which the diacidic motif appears (Padmanabhan et al, 2018). In fact, a quick reanalysis of the multiple sequence alignments from the homologs of SOD1, Acb1 (Cruz-Garcia et al, 2017) by focusing on the mammalian sequences alone shows that they all have a common triacidic motif (Figure 1).…”
Section: Discussion Triacidic Motif Is Potentially a Signal For Ucps ...mentioning
confidence: 65%
See 2 more Smart Citations
“…Of these two statistically significant observations, the triacidic motif, by coincidence, happens to be an extension of the observation of the diacidic motif (Cruz-Garcia et al, 2017) and our earlier attempt to find the context in which the diacidic motif appears (Padmanabhan et al, 2018). In fact, a quick reanalysis of the multiple sequence alignments from the homologs of SOD1, Acb1 (Cruz-Garcia et al, 2017) by focusing on the mammalian sequences alone shows that they all have a common triacidic motif (Figure 1).…”
Section: Discussion Triacidic Motif Is Potentially a Signal For Ucps ...mentioning
confidence: 65%
“…Thus, it appears that triacidic or KKX amino acid motifs in the proximity of LIR and/or phosphorylatable amino acids may play a significant role in triggering the unconventional secretion. This result was also validated in the independently curated dataset of unconventionally secreted proteins from other mammalian cells (Padmanabhan et al, 2018), where among the 26 mammalian proteins that are secreted unconventionally, 5 of them had triacidic motifs within a 5 amino acid proximity of LIR. 9 of the remaining proteins where there was no sequence proximity, but the structures were available, had LIR motifs within 10 Å of the triacidic motif, and three other structures had them within 15 Å.…”
Section: Deriving the Hypothesis For The Signal For Ucpsmentioning
confidence: 57%
See 1 more Smart Citation
“…However, presence of existing ER export motifs should not be solely used to predict export of proteins. For instance, a study identified 100 cargoes that contained putative diacidic motifs and proposed that the functional ER export diacidic motifs seem to appear in a region with ordered structure and higher hydrophobicity 95 . The importance of the dihydrophobic nature, rather than the specific residues, of the ER exit signal 'FF' in ERGIC‐53 was found by replacing the di‐phenylalanine 'FF' motif by di‐tyrosine 'YY', di‐valine 'VV', di‐isoleucine 'II' or di‐leucine 'LL' which mediated transport as efficiently if not more than the 'FF' motif 80,96 .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Likewise, the specific phosphorylation of the small heat shock protein, α-Crystallin B at the Ser59 residue enhances autophagy mediated secretion ( D’Agostino et al, 2019 ). The discovery of the diacidic motif, DE as the signal for UCPS ( Cruz-Garcia et al, 2017 ) along with the context dependence of the presence of this motif in proximity with the LIR motif ( Padmanabhan et al, 2018 ) might provide some clues. With the DE as the UCPS export signal, the LIR containing proteins possess specific membrane associated receptors and the cells might use this in combination for the type III secretion.…”
Section: Key Research Perspectivesmentioning
confidence: 99%